Numb chin syndrome as initial symptom of T-cell acute lymphoblastic leukemia in a 14-year-old female: A case report - Elizabeth G.K. Floodeen; Marshall F. Newman; Rafik Abdelsayed; Pratikkumar Patel (Oral and Maxillofacial Surgery Cases, 2022)
Numb chin syndrome (NCS) has been described in the context of known malignancy or as a signal of disease recurrence; however, it is unusual to be the initial presenting symptom of malignancy. We offer a case report of an otherwise healthy 14-year old female who presented with NCS of seven months duration. Radiographic imaging showed a ill-defined “moth eaten” appearance of the mandible and incisional biopsy showed diffuse lymphocyte infiltrates. Immunohistologic staining performed was consistent with T-cell acute lymphoblastic leukemia/lymphoma (T-ALL), which was later confirmed with bone marrow aspirate. While traditionally the diagnosis of lymphoma was reserved only for bulky lesions with minimal disease of the peripheral blood and bone marrow, current trends have shifted to group lymphoblastic leukemia and lymphoma as a single disease process spectrum. After a review of the literature, no reports were identified of NCS as the only presenting symptom of T-ALL in a previously healthy child. We therefore propose an algorithm to guide clinicians in an accurate and timely diagnosis of this common pediatric malignancy.